Establishment of intercropping of beet and chicory depending on soil management - Coutinho, Pablo Wenderson; Oliveira, Paulo Sérgio; Eche, Márcia; Cadorin, Danielle; Vanelli, Jaqueline (Revista Ciência Agronômica, 2017)
This study aimed to evaluate the productivity and quality characteristics of beet and chicory based on management of straw and intercropping period of establishment. The experiment was conducted in the organic horticulture sector of UNIOESTE, in a design of randomized blocks with four replications, where the treatments were arranged in 2 x 5 and 2 x 8 factorial schemes. The first factorial consisted of the straw mulch management (with and without incorporation of the gray velvet bean straw) and the intercropping period of establishments and beet and chicory monocrops (0; 7; 14 and 21 days after transplanting beet). The second factorial was composed of the straw mulch management (with and without incorporation) and the cultivation of chicory intercropped with beet and in monocrop at the same periods. The chicory interfered in beet’s productivity when the transplant occurred at the same period. The beet cultivation in a intercropping contributed positively to the better use of the area in the two management systems, influencing in a positive way the agronomic characteristics of the crop, but without compromising the commercial quality of the crops, that were agronomically viable, considering the UET index.